Supply of goods free of charge in value added tax system - Milošević Miloš (Anali Pravnog Fakulteta u Beogradu)
Consideration represents one of the cumulatively prescribed conditions for the taxation of supplies of goods in value added tax system. In the absence of consideration there is in general no basis for taxation, which makes room for untaxed final consumption - the case in which a taxpayer deducts input VAT on purchased good that is subsequently used for his own or another person's final consumption free of charge. In this paper, the author analyzes the situations in which, for taxation purposes, the supplies of goods free of charge will be treated equally as supplies for consideration and, relying on the jurisprudence of the European Court of Justice, notes the deviations of the domestic practice from the communautaire one, while providing concrete recommendations for their elimination.